2020
DOI: 10.1007/s00401-020-02125-x
|View full text |Cite
|
Sign up to set email alerts
|

Picalm reduction exacerbates tau pathology in a murine tauopathy model

Abstract: Genome-wide association studies (GWAS) have identified PICALM as one of the most significant susceptibility loci for late-onset Alzheimer's disease (AD) after APOE and BIN1. PICALM is a clathrin-adaptor protein and plays critical roles in clathrin-mediated endocytosis and in autophagy. PICALM modulates brain amyloid ß (Aß) pathology and tau accumulation. We have previously reported that soluble PICALM protein level is reduced in correlation with abnormalities of autophagy markers in the affected brain areas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…All these antibodies were diluted in the washing buffer supplemented with 5% of bovine serum and 0.02% azide. The rabbit polyclonal antibody B19 that recognizes all isoforms of tau 83,84 (kindly provided by Jean-Pierre Brion, Université libre de Bruxelles) was diluted at 1/2,000 in PBS supplemented with 2% BSA and 0.08% azide. Diluted antibodies were incubated with the membranes overnight under agitation at 4 °C.…”
Section: Western Blot 20 μG Of Protein Lysates or Samples Collected mentioning
confidence: 99%
“…All these antibodies were diluted in the washing buffer supplemented with 5% of bovine serum and 0.02% azide. The rabbit polyclonal antibody B19 that recognizes all isoforms of tau 83,84 (kindly provided by Jean-Pierre Brion, Université libre de Bruxelles) was diluted at 1/2,000 in PBS supplemented with 2% BSA and 0.08% azide. Diluted antibodies were incubated with the membranes overnight under agitation at 4 °C.…”
Section: Western Blot 20 μG Of Protein Lysates or Samples Collected mentioning
confidence: 99%
“…Recent studies have shown that the phosphatidylinositol-binding clathrin assembly protein (PICALM) is involved in tau autophagy and clearance [ 96 , 97 ]. PICALM has also been found to be involved in autophagy in vivo and in vitro, including elongation of phagocytes, formation of autophagosomes, and fusion between autophagosomes with lysosomes [ 98 , 99 ].…”
Section: Autophagy and Nddsmentioning
confidence: 99%
“…The sarkosyl-soluble supernatant was removed, and sarkosylinsoluble pellets were rinsed briefly with 500 μl of 50 mM Tris-HCl (pH 7.4) and re-suspended in 200 μl of 50 mM Tris-HCl (pH 7.4) by vigorous pipetting. Sarkosylinsoluble fractions were analysed by western blotting (WB) and transmission electron microscopy as previously described [3,4].…”
Section: Preparation Of Brain Homogenates For Biochemical Analysismentioning
confidence: 99%